The Use of Relative Statistical Indicators, of Central Trend Indicators and Their Interpretation - Cristina Ioana Antik (Agora International Journal of Economical Sciences (AIJES), 2018)
Statistics is one of the economic evidence form in charge with the study of socioeconomic staple phenomenons, quantitatively speaking, in close connection with their qualitative side, in concrete conditions of space and time. The present article uses the importance of statistical indicators in the economic analysis of an economic entity, showing the calculation of theoretical and practical relative indicators, and the central trend indicators.
Keywords: 330